-2x-23=2x+1

Simple and best practice solution for -2x-23=2x+1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2x-23=2x+1 equation:


Simplifying
-2x + -23 = 2x + 1

Reorder the terms:
-23 + -2x = 2x + 1

Reorder the terms:
-23 + -2x = 1 + 2x

Solving
-23 + -2x = 1 + 2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-2x' to each side of the equation.
-23 + -2x + -2x = 1 + 2x + -2x

Combine like terms: -2x + -2x = -4x
-23 + -4x = 1 + 2x + -2x

Combine like terms: 2x + -2x = 0
-23 + -4x = 1 + 0
-23 + -4x = 1

Add '23' to each side of the equation.
-23 + 23 + -4x = 1 + 23

Combine like terms: -23 + 23 = 0
0 + -4x = 1 + 23
-4x = 1 + 23

Combine like terms: 1 + 23 = 24
-4x = 24

Divide each side by '-4'.
x = -6

Simplifying
x = -6

See similar equations:

| 3x+5+y=100 | | 3x+y-5=100 | | 8s+2s=20 | | 19d-15d=16 | | 38-f=-30 | | -x+23=2x+8 | | 3(m+3)+24=69 | | 2x+x+y=100 | | 7x(12/6-2)^2-6 | | h-27/-7=-9 | | 7x+55=3x+23 | | 9(m+1)=54 | | 3(s+22)+10=88 | | -12/r=-3 | | -c^2+c+30=0 | | -3(s+18)=-15 | | 6x+40=2x+4 | | 6(k-74)-5=83 | | 6=4-w | | x+17=5x+5 | | 6=-3(d-9) | | 2(7x+8)-4=28 | | 288=X+0.06X | | t-7/3=3 | | 4x+31=x+7 | | 12/n=3 | | 4x+11=x+1 | | 2/3x5/6x | | 8-51nx=3 | | 5x-26=x+6 | | x+(x*0.3)=5540.12 | | (x+(x*0.3))=5540.12 |

Equations solver categories